Effects Of Cutting Parameters On Acoustic Emission Signal Response During Drilling Of Laminated Composites Using Factorial Design Method (Journal of Science and Technology, 2016)
Factorial design has been used to study the effect of cutting parameters on acoustic emission signal response during the drilling of composite laminates. Experimental design is a strategy of planning, conducting, analyzing and interpreting experiments so that sound and valid conclusion can be drawn efficiently, and economically. In this study, effects of cutting speed, feed rate and tool diameter on the acoustic emission signal response are investigated using acoustic emission\'s energy, amplitude, root mean square and frequency responses and 23factorial design for drilling operation. Cutting tests were performed under dry conditions. Calculated effects, standard errors at 95% confidence level, and models governing the acoustic emission response to the cutting conditions have been generated from the acoustic emission signal responses. The results revealed that, acoustic energy response has significant effects due to the cutting parameters. Hence a model can be established to relate the acoustic emission\'s energy response and the cutting parameters, and as a result monitor and control the area of delamination during the drilling process.